2018
DOI: 10.18517/ijaseit.8.4.5028
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Ad-Hoc On-Demand Distance Vector and Optimized Link State Routing Protocols in Mobile Ad-Hoc Networks

Abstract: Mobile Ad-hoc Networks (MANETs) are self-sufficient networks that can work without the need for centralized controls, pre-configuration to the routes or advance infrastructures. The nodes of a MANET are autonomously controlled, which allow them to act freely in a random manner within the MANET. The nodes can leave their MANET and join other MANETs at any time. These characteristics, however, might negatively affect the performance of the routing protocols and the overall topology of the networks. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Each hop crossed by the routing message during the transportation is considered as one transmission. The following equation has used to calculate NRL [4,27].…”
Section: Performance Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each hop crossed by the routing message during the transportation is considered as one transmission. The following equation has used to calculate NRL [4,27].…”
Section: Performance Metricsmentioning
confidence: 99%
“…A MANET is a collection of wireless nodes that can dynamically form a network to exchange information without using any pre-existing fixed network infrastructure [1][2][3]. Each node in MANET uses its transmission range to send and receive packets [4,5]. Routing paths in mobile ad-hoc networks potentially contain multiple hops and some nodes are unable to communicate directly with other remote nodes because the transmission range of each node in the MANET is limited.…”
Section: Introductionmentioning
confidence: 99%
“…With these capacities, MANET hubs straightforwardly or by implication converse with one another over a radio transmission range. The irregular (or random) versatility attribute of the system and radio transmission range between the hubs significantly alter the system topology, time plan as well as areas of the remote gadgets [15][16][17]. A basic case of the MANET topology is as in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…To locate a path from the source to the destination, the standard on-demand ad hoc routing algorithms has initiated a complete route discovery process. [9][10][11][12] In literature, there are many geographic routing protocols proposed, and it has been revealed that substantial performance enhancements are produce by them when allied with standard on-demand routing algorithms. For scalable routing, an ideal solution is provided by the geographic routing, which includes a location service and a strategy of geographic forwarding.…”
Section: Introductionmentioning
confidence: 99%